Primary cilia-associated protein IFT172 in ciliopathies - Zheng, Nan-Xi; Miao, Ya-Ting; Zhang, Xi; Huang, Mu-Zhi; Jahangir, Muhammad; Luo, Shilin; Lang, Bing (Frontiers in Cell and Developmental Biology, 2023)
Cilium is a highly conserved antenna-like structure protruding from the surface of the cell membrane, which is widely distributed on most mammalian cells. Two types of cilia have been described so far which include motile cilia and immotile cilia and the latter are also known as primary cilia. Dysfunctional primary cilia are commonly associated with a variety of congenital diseases called ciliopathies with multifaceted presentations such as retinopathy, congenital kidney disease, intellectual disability, cancer, polycystic kidney, obesity, Bardet Biedl syndrome (BBS), etc. Intraflagellar transport (IFT) is a bi-directional transportation process that helps maintain a balanced flow of proteins or signaling molecules essential for the communication between cilia and cytoplasm. Disrupted IFT contributes to the abnormal structure or function of cilia and frequently promotes the occurrence of ciliopathies. Intraflagellar transport 172 (IFT172) is a newly identified member of IFT proteins closely involved in some rare ciliopathies such as Mainzer-Saldino syndrome (MZSDS) and BBS, though the underpinning causal mechanisms remain largely elusive. In this review, we summarize the key findings on the genetic and protein characteristic of IFT172, as well as its function in intraflagellar transport, to provide comprehensive insights to understand IFT172-related ciliopathies.